Mediating Effect of Interest on Gen Z’s Stock Investment Decisions in Central Jakarta - Dila Aprilia; Alyta Shabrina Zusryn; Siti Marhamah (Journal of Accounting, Management, and Economics Research (JAMER), 2027)
The study is structured with the primary aim of investigating specific relationships and underlying patterns how understanding of investing and motivational drivers shapes stock investment choices, where interest in investing functions as an intermediary factor among Generation Z in Central Jakarta. The study respondents were 132 stock investors who had made stock purchases and were participants were determined using a criterion-based selection approach. By utilizing the PLS-SEM analytical technique, the study revealed positive effects of investment knowledge and investment motive on stock investment behavior among individuals. Moreover, it was also observed that both variables played an enhancing role in increasing investment interest. It was confirmed that investment interest serves as an intermediary linking knowledge of investment and investment motivation on stock investment decisions. These findings indicate that increasing investment knowledge and motivation can encourage higher investment interest, which has an impact on stock investment decision-making. Appropriate investment knowledge and motivation shape interest as a form of intention, which in turn encourages the birth of more rational and considered stock investment decisions.